The Importance of Representing STEM Professional Role Models Through Multimedia Instructions - Marito Tamba, Riris; Ling, Chia (KnE Social Sciences, 2024)
The first part of this paper discusses that STEM education does not have clearly defined fields, unlike discipline-based educational programs such as science education, which do have clearly defined areas. In order to overcome the complexity and ambiguity of different STEM and STEM education perspectives, it is necessary to understand the status and trajectory of STEM education research. Also, the authors suggest that stereotypes about STEM professionals can be minimized by using several faces associated with learners, as role models in presenting information about the career options available to STEM professionals in order to reduce stereotypes. As learners learn STEM, they can recognize their potential and their sense of self as well as their STEM connections. Additionally, by exposing students to various professions through multimedia learning, the distance between role models and learners may be closed, thus appealing to their interests and encouraging them to pursue careers that they are interested in the future. Keywords: STEM, professional role models, multimedia instructions